Analysis of production animal notifiable diseases from 2018 to 2022: a systematic review (Research, Society and Development, 2023)
The objective of this review was to know the studies carried out in the last five years on the diseases of mandatory notification to WOAH in terrestrial production animals to identify the main diseases, animal species involved, the countries where the studies were located, and diagnostic methods used. A systematic approach of observational studies was used in open access articles. Criteria were adopted for inclusion, exclusion and scoring of articles. The search on evidence sources returned 1062 references. After removal of duplicates and exclusion in Phases I and II, 37 articles were analyzed after reading the full texts for data characterization. The results were evaluated by animal species, country, types of disease (zoonotic/non-zoonotic) and agent (bacteria/virus). The findings showed diseases such as: PRRS (18/54; 33.33%), Aujeszky's Disease (04/54; 07.41%) and Avian Infectious Bronchitis (03/54; 05.56%) among those of economic; Rift Valley Fever (04/54; 07.41%), Brucellosis (03/54; 5.56%) and Japanese Encephalitis (02/54; 03.70) among zoonoses. China (8/37; 21.62%) was the country that stood out the most in terms of diversity of studies. This review demonstrated a complex of disease pathogens in birds, ruminants and swine in different countries, contributing to an updated demonstration of scientifically based data as support for future studies on the subject studied.